ANALYSIS OF THE ROLE OF PERSONAL FINANCIAL MANAGEMENT KNOWLEDGE AND SELF-EFFICACY ON STUDENT ENTREPRENEURIAL INTENTIONS - Heri Erlangga (Jurnal Ekonomi, 2023)
This study seeks to establish 1) the influence of personal financial management on entrepreneurial ambitions, 2) the influence of self-efficacy on entrepreneurial intentions, and 3) the influence of personal financial management and self-efficacy on entrepreneurial intentions. This study is an explanation study. The sample consists of 100 students from a population of 247 Management Study Program, Faculty of Economics, University of BSI students who have attended Entrepreneurship courses. The study concluded that personal financial management has an effect on entrepreneurial intentions, self-efficacy has an effect on entrepreneurial intentions, and personal financial management and self-efficacy have an influence on entrepreneurial ambitions. Moreover, personal financial management and self-efficacy contributed 67.2% to changes in entrepreneurial ambitions, with the remaining 32.8% influenced by variables not examined in this study.